Estimation of Time Since Injuries (Age of Wound) in Living Medico-Legal Cases of Mansehra (Medical Forum Monthly, 2024)
Objective: The objective was to study the way in which duration of injury or time since injury (age of the wound) is assessed in live medico legal cases in rural area, to know and analyze the time since injury recorded in Medico Legal register and have an idea that how much time later the injured person is examined after injury or how much time later he reach to a doctor for opinion of duration of injury and other opinion..Study Design: Retrospective study.Place and Duration of Study: This study was carried out at a medico legal centre of Mansehra District from January to August of 2005.Materials and Methods: The study is a record based research, 100 cases were selected, which were consecutively recorded from the previously registered MLC cases in a center of Mansehra district. Data of time since injury or duration of injury (age of the wound) along with preliminary data was recorded from the record and analyzed.Results: In 100 cases the time since injuries were 0 to 59 minutes, 1hour to 6 hours, 7 hours to 12 hours, 13 hours to 24 hours and others. Among the victims having 25 years of age only one1 (1%) had times of injury of 0 to 59 Minuit’s, of age of 26year to 45 year only 2(2%) were having time of 0 to 59 mints and no one above 45 years of age has the same time. 35 (35%) cases of age 25 years were having time since injury of 1 to 6 hours, 33(33%) cases of age 26 to 45 years were having same time and only 5 of above the age of 45 years had duration of injury of 1 to 6 hours. 17(17%) of all the cases has age of injury up to 7 to 12 hours. 7 (7%) of total cases has time of 13 to 24 hour.Conclusion: Our study reflect the true situation of subjected society where the hospital is in the reach of population and this also reflect upon some influence of injured person act 2004, according to which the victim shall be taken to hospital for treatment as early as possible and the legal matter can be dealt with later on , among male victims 2(2%) and among female 1(1%) has age of wounds of 0 to 59mints mean less than one hour, 48(48%) male and 25(25%) female had age of wound of 1 to 6 hours, 1(1%) female and 6(6%) male were having time of injury of 13 to 24 hours.